If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + 4n + -3m + 8n = 0 Reorder the terms: 7m + -3m + 4n + 8n = 0 Combine like terms: 7m + -3m = 4m 4m + 4n + 8n = 0 Combine like terms: 4n + 8n = 12n 4m + 12n = 0 Solving 4m + 12n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12n' to each side of the equation. 4m + 12n + -12n = 0 + -12n Combine like terms: 12n + -12n = 0 4m + 0 = 0 + -12n 4m = 0 + -12n Remove the zero: 4m = -12n Divide each side by '4'. m = -3n Simplifying m = -3n
| 5x+8x+4y+2y= | | x^4+16i=0 | | -5x+8y-4= | | 3x=-80 | | 53-3x=11-10x | | (2x-1)(x+1)=0 | | 14+4(x+1)=26 | | (2x-1)x(x+1)=0 | | 2a+30=50 | | 3x(4x-5)+3=0 | | 5x^2+3x-28=0 | | 10x^2+0.2x+200=0 | | v=axt | | 20x+12y-28= | | 5d-30+40= | | -5y+-15= | | 160=(2w+14)w | | x^3=40 | | 24x+16=19 | | 7r+56= | | 7r+8= | | 3b-6-12b-7= | | -8(2t+9)=-168 | | 4(f-5)=-4 | | (x+4)(3-5x)=6-3(x-1) | | (5x-10)=6x+5 | | -(3x-7y+1)= | | x=1287.4(17)+48470 | | 2(x-10)+(x-10)=46 | | 2(6x+2)=0 | | x^2+84-520=0 | | (3x-1)(2x+1)=0 |